Introduction to modern climate change - Dessler, Andrew Emory (New York : Cambridge University Press, 2012)
"This book is aimed at non-science-major undergraduates and is tightly focused on the problem of anthropogenic climate change. The first half of the book focuses on the science of modern climate change, including evidence that the Earth is warming and a basic description of climate physics. It also covers concepts like radiative forcing, feedbacks, and the carbon cycle. The book shows many algebraibased calculations to illustrate the science. The second half of the book goes beyond science to address non-science issues such as the economics and our policy options to address climate change. The goal of the book is for a student to leave the class ready to engage in the public policy debate on this issue"--Provided by publisher.
Formerly CIP.
Includes bibliographical references (p. 231-233) and index.
Keywords: Climatic changes; Climatic changes -- Government policy